Auditoría tributaria para disminuir el riesgo tributario en la empresa L&M de seguridad privada Cia. Ltda. periodo 2017 - Carrasco García, María Belén (2018)
The investigation stars from the approach to the problem and detailing the status of the company with the various difficulties it is going through, then it is justified why it is important to carry out this tax audit. With regard to the theoretical framework it is made know the company’s background, researches related to the theme, concepts related to the research, supported by the respective bibliography. The methodology used to develop the research is the inductive type with a non-experimental design based on a quantitative approach (numerical data). The population and sample we used were documentary and personnel. Regarding the results and discussion, methods, procedures and audit techniques were applied taking into account the tax legislation and the accounting information delivered by the company. Finally, the particular conclusions and recommendations were made based on the findings obtained during the execution of the audit.